The Impact of Teaching Resources on the Use of Different Teaching Methods: Libyan Accounting Graduates’ Perceptions - Alfatiemy, Mohamed Moftah; Norwani, Norlia Mat; Yusof, Rohaila (International Journal of Economics, Business and Management Studies, 2012)
This study aims to investigate the perceptions of Libyan accounting graduates regarding the teaching methods that Libyan accounting educators practiced in their classrooms, the adequacy of teaching and learning resources at Libyan universities, and to test whether or not there is any relationship between adequacy of teaching and learning resources at Libyan universities and the teaching methods used by Libyan accounting educators. Quantitative data was collected from fifty four Libyan postgraduate students. Findings revealed that accounting graduates reported a high level application of teacher-centered methods than learner-centered methods at Libyan universities. Furthermore, accounting graduates in this study indicated the inadequacy of vital teaching resources. While, no one of the teaching resources indicated a significant relationship with the teacher-centered teaching methods, the learner-centered teaching methods showed positive and significant relationship with most of these teaching resources. As these teaching methods need some special resources such as laptops, internet, computers, and so on, indeed, lack of these resources will hinder the use of such teaching methods. This study helps readers better understand the teaching effectiveness in the Libyan context and provides data for future comparative studies regarding the teaching strategies in accounting.